Effect of Intensity and Mode of Artificial Upwelling on Particle Flux and Carbon Export - Baumann, Moritz; Taucher, Jan; Paul, Allanah J.; Heinemann, Malte; Vanharanta, Mari; Bach, Lennart T.; Spilling, Kristian; Ortiz, Joaquin; Arístegui, Javier; Hernández-Hernández, Nauzet; Baños, Isabel; Riebesell, Ulf (Frontiers in Marine Science, 2021)
Reduction of anthropogenic CO2 emissions alone will not sufficiently restrict global warming and enable the 1.5°C goal of the Paris agreement to be met. To effectively counteract climate change, measures to actively remove carbon dioxide from the atmosphere are required. Artificial upwelling has been proposed as one such carbon dioxide removal technique. By fueling primary productivity in the surface ocean with nutrient-rich deep water, it could potentially enhance downward fluxes of particulate organic carbon (POC) and carbon sequestration. In this study we investigated the effect of different intensities of artificial upwelling combined with two upwelling modes (recurring additions vs. one singular addition) on POC export, sinking matter stoichiometry and remineralization depth. We carried out a 39 day-long mesocosm experiment in the subtropical North Atlantic, where we fertilized oligotrophic surface waters with different amounts of deep water. The total nutrient inputs ranged from 1.6 to 11.0 μmol NO3– L–1. We found that on the one hand POC export under artificial upwelling more than doubled, and the molar C:N ratios of sinking organic matter increased from values around Redfield (6.6) to ∼8–13, which is beneficial for potential carbon dioxide removal. On the other hand, sinking matter was remineralized at faster rates and showed lower sinking velocities, which led to shallower remineralization depths. Particle properties were more favorable for deep carbon export in the recurring upwelling mode, while in the singular mode the C:N increase of sinking matter was more pronounced. In both upwelling modes roughly half of the produced organic carbon was retained in the water column until the end of the experiment. This suggests that the plankton communities were still in the process of adjustment, possibly due to the different response times of producers and consumers. There is thus a need for studies with longer experimental durations to quantify the responses of fully adjusted communities. Finally, our results revealed that artificial upwelling affects a variety of sinking particle properties, and that the intensity and mode with which it is applied control the strength of the effects.